Desde los últimos confines: nueva especie de lagartija Liolaemus (Iguania: Liolaemidae) de la estepa patagónica de Santa Cruz, Argentina - San Millán, Agustina (2024)
new species of lizard of the genus Liolaemus is described. It inhabits the Patagonian steppe at the eastern of Santa Cruz Province, Argentine. Characters of external morphology, morphometry, coloration pattern and pholidosis were used for its description. In addition, phylogenetic proposals based on morphological and molecular evidence that distinguishes the proposed species from other closely related species are presented. This new lizard belongs to the L. boulengeri group, L. melanops clade, L. telsen subclade. It is a small species in relation to other species of the same genus, and its coloration pattern is distinctive within the L. telsen subclade. This combination of characters supports the candidate species as a unique species within the genus. The taxon described in this study was previously classified within the range of Liolaemus boulengeri. However, the molecular and morphological evidence presented in this study, added to those from works clearly indicates the validity as a new species of Liolaemus.